Does a Bank's History Affect Its Risk-Taking? - Bouwman, Christa H. S.; Malmendier, Ulrike (American Economic Review, 2015)
We ask whether past macro-economic and bank-specific shocks experienced and survived by a bank affect its current capitalization and risk-taking. Using Call Report data from 1984 to 2010, we find that a bank's experience shapes its capital structure and risk appetite. Banks that have survived periods of undercapitalization tend to implement higher equity ratios and take less risk in the periods following such crises, as measured by net charge-offs, non-performing loans, or earnings volatility 10-25 years later. However, observing high rates of failure among other banks stirs banks in the opposite direction. The evidence is suggestive of institutional memory affecting banks' capital and risk-taking.